2018
DOI: 10.1007/s00330-018-5332-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing internal herniation after laparoscopic Roux-en-Y gastric bypass: usefulness of systematically reviewing CT scans using ten signs

Abstract: • Computed tomography is useful to diagnose internal herniation(IH) after gastric bypass surgery • Ten signs are described to improve CT diagnosis of IH • Systematically reviewing CT scans improves specificity • There is no difference in experience levels when using these ten signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Our findings confirm the assumptions of previous studies, that also found that structured reporting using CT signs improved accuracy [14,16]. However, these previous studies performed blind reading of the CT scans retrospectively and compared them with the original report.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings confirm the assumptions of previous studies, that also found that structured reporting using CT signs improved accuracy [14,16]. However, these previous studies performed blind reading of the CT scans retrospectively and compared them with the original report.…”
Section: Discussionsupporting
confidence: 90%
“…Most noteworthy, the sensitivity of the swirl sign decreased compared to most previous studies with a comparable increased specificity. However, the accuracy is comparable to a previous study into the ten CT signs, 89.7% compared to 86.5-91.4% [14]. The accuracy of small bowel obstruction, clustered loops, right-sided anastomosis, and enlarged nodes decreased compared to this previous retrospective study.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations